Interaction of a Transapical Miniaturized Ventricular Assist Device With the Left Ventricle: Hemodynamic Evaluation and Visualization in an Isolated Heart Setup. Issue 12 (26th May 2016) - Granegger, Marcus; Aigner, Philipp; Haberl, Thomas; Mahr, Stephane; Tamez, Daniel A.; Graham, Joel; Nunez, Nathalie J.; Schima, Heinrich; Moscato, Francesco
Abstract: New left ventricular assist devices (LVADs) offer both important advantages and potential hazards. VAD development requires better and expeditious ways to identify these advantages and hazards. We validated in an isolated working heart the hemodynamic performance of an intraventricular LVAD and investigated how its outflow cannula interacted with the aortic valve. Hearts from six pigs were explanted and connected to an isolated working heart setup. A miniaturized LVAD was implanted within the left ventricle (tMVAD, HeartWare Inc., Miami Lakes, FL, USA). In four experiments blood was used to investigate hemodynamics under various loading conditions. In two experiments crystalloid perfusate was used, allowing visualization of the outflow cannula within the aortic valve. In all hearts the transapical miniaturized ventricular assist device (tMVAD) implantation was successful. In the blood experiments hemodynamics similar to those observed clinically were achieved. Pump speeds ranged from 9 to 22 krpm with a maximum of 7.6 L/min against a pressure difference between ventricle and aorta of ∼50 mm Hg. With crystalloid perfusate, central positioning of the outflow cannula in the aortic root was observed during full and partial support. With decreasing aortic pressures the cannula tended to drift toward the aortic root wall. The tMVAD could unload the ventricle similarly to LVADs under conventional cannulation. Aortic pressure influenced central positioning of the outflow cannula in the aortic root. The isolated heart is a simple, accessible evaluation platform unaffected by complex reactions within a whole, living animal. This platform allowed detection and visualization of potential hazards.